IMPROVING LEARNING OUTCOMES USING CANVA AND WORDWALL BASED LEARNING MEDIA FOR PANCASILA EDUCATION SUBJECTS IN CLASS IV MI NURUL HUDA 3 BOGOR CITY - Feby Andiyanty; Fadil, Khaidir; Dewi, Reni Sinta (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
This study aims to improve the learning outcomes of students in Pancasila Education subjects by using Canva and Wordwall learning media in class IV MI Nurul Huda 3 Bogor City. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model (1988) which is carried out in two cycles consisting of planning, action, observation and reflection. Data collection techniques in this study are observation, learning outcome tests, and documentation. This study shows that before the implementation of the action, the learning completeness of students was still low, namely only 42% with an average value of 63. After the use of Canva and Wordwall media in their learning, there was a significant increase. In cycle I, the percentage of student learning completeness increased to 74% with an average value of 76, and increased again in cycle II to 90% with an average value of 85. In addition to the increase in learning outcomes, the active involvement of students and teacher activities also progressed. In cycles I and II, teacher activity increased from 95% to 100%, while student participation increased from 80% to 85%. This shows that the Canva media has proven to support the delivery of material visually and attractively, while the wordwall provides an interactive and enjoyable learning evaluation experience. Overall, the use of these two media not only has an impact on increasing learning outcomes quantitatively, but also contributes to increasing student motivation, enthusiasm, and self-confidence in participating in the learning process.